UPAYA GURU MENGEMBANGKAN MINAT DAN BAKAT PESERTA DIDIK DENGAN MOTIVASI BELAJAR RENDAH DI KELAS - Marzuki; Siti Fadila Azwari Sihombing; Purnama; Sutarum; Mutiara Sari Rahmadani Hrp (Yayasan Baitul Hikmah al-Zain, 2026)
This research discusses teachers' efforts to develop the interests and talents of students with low learning motivation in the classroom. The main issue raised is how teachers can help students who are less enthusiastic about learning so that their potential does not develop optimally. Low learning motivation often leads to low participation, declining academic performance, and hindered development of students' interests and talents. This research uses a qualitative approach with a descriptive method, which involves classroom observation, in-depth interviews with teachers, and analysis of learning documentation. The research findings indicate that teachers employ several important strategies, such as creating an engaging, enjoyable, and varied learning environment to enhance student attention. Teachers also take an individual approach to understand the needs, obstacles, and emotional conditions of the students. Additionally, providing positive reinforcement is a way to foster self-confidence and motivate them in the learning process. In addition, teachers collaborate with parents and school staff to provide a variety of activities that align with students' interests and talents, giving them space to explore their abilities in a more focused manner. This finding confirms that sustained teacher support and the implementation of appropriate learning strategies can enhance student engagement and optimally foster the development of interests and talents.